Real Air-Conditioning Performance of Ejector Refrigerator Based Air-Conditioner Powered by Low Temperature Heat Source - Tongchana Thongtip; Natthawut Ruangtrakoon (Energies, 2021)
In this present work, the air-conditioning test performance of an ejector refrigerator-based air-conditioner (ERAC) was proposed. The ERAC was operated as the water chiller to produce the cooling load up to 4.5 kW. The chilled water temperature was later supplied to the fan-coil unit for producing the thermal comfort condition. The cooling water used to cool the condenser was achieved from the cooling tower which was operated under the hot and humid ambient. This is to demonstrate the feasibility of using the ERAC in real working conditions. The cooling load supplied to the air-conditioned space was applied by the air heater. The ERAC could efficiently be operated to produce the thermal comfort condition which was driven by the hot water temperature (Thot) of 90–98 °C. The system performance could vary with the heat source temperatures, cooling load, primary nozzle, and air-conditioned space temperature. The optimal performance was determined when varying the Thot, and, hence, the optimal Thot was indicated. The optimal Thot varied significantly with variations in the working condition. The test results demonstrated high potential to further using the ejector refrigeration system in the actual air conditioning application.
Keywords: Refrigeration and Air Conditioning Technologies; Building Energy and Comfort Optimization; Heat Transfer and Optimization